PENDIDIKAN AKUNTANSI FORENSIK DAN INVESTIGASI PENIPUAN - Hasna Hanifah; Harti Budi Yanti (STMIK Widuri Jakarta, 2023)
The high number of fraud casesthat have occurred in Indonesia, both in the financial and public sectors, has caused a lot of harm to the people of Indonesia, and is also a concern for the global world. The high cases of fraud require forensic accountants who are reliable in their fields, including in investigating fraud that occurs in a company/organization in Indonesia. This study describes several formulations of the problem, including whether forensic accounting affects the performance of the forensic auditor, whether the ability offraud investigations affects the performance of the forensic auditor, and finally whether the experience of knowledge and skills of forensic investigation. This research has important roles and implications for readers, especially for auditors, forensic accountants, and fraud investigators. The type of data collection technique used by researchers is primary data by distributing questionnaires to S1 Accounting students who are actively registered at universities in Indonesia. The results obtained in this study are that Forensic Accounting Education as well as Fraud Investigation has an effect on Forensic Auditor Performance. The researcher recommends to future researchers to implement and develop the results of this study so that the results of this study are better.